PENGESANAN KENYAHWUJUDAN NAJIS BERDASARKAN KAEDAH ANALISIS PROFIL DNA FORENSIK: SATU ANALISIS HUKUM: Detection of Excrement Degradation Based on Forensic DNA Profiling Method: An Analysis from Fiqh View - Mahaiyadin, Mohd Hapiz; Suhaimi, Roshaimizam; Mahmood, Ainorkhilah; Ismail, Nor Fariza; Mohd Radzi, Hisyam (Jurnal Syariah, 2020)
Nowadays, some people have doubts about the ability of washing machine and laundry machine to remove impurities (najīs) because the use of these machines has never been discussed by fuqahā’ in the past. Therefore, this study is aimed at identifying the existence of impurities after washing according to the method of purification of Shāfi‘i’s madhhab. Three samples of blood, urine and baby stool were used on the clothes. All samples were tested using two methods - the Kestle-Meyer Test (KM-Test) and Forensic DNA Profile Analysis at the Penang State Department of Chemistry Forensic Lab. The results of the KM-Test test on blood samples have shown negative results. While urine samples and baby stools cannot be detected directly. In addition, the DNA profile analysis also showed similar results that before washing, the presence of najis in blood control samples was detected only at 44.80 ng / μl (sample A) and 65. 00 ng / μl (sample B) and after washing, the effect on samples A and B in the laundry wash were only 1.78 ng / μl and 3.28 ng / μl. While in the washing machine, there were only 3.28 ng / µl in sample A and 1.11 ng / µl in sample B. Furthermore, this study concluded that washing machine and laundry machine successfully remove the impurities from clothing.